Directly Acting Antivirals for COVID-19: Where Do We Stand? - Teoh, Siew L.; Lim, Yi H.; Lai, Nai M.; Lee, Shaun W. H. (Frontiers in Microbiology, 2020)
The outbreak of a novel coronavirus (SARS-CoV-2) in Wuhan, China in December 2019 has now become a pandemic with no approved therapeutic agent. At the moment, the genomic structure, characteristics and pathogenic mechanisms of SARS-CoV-2 have been reported. Based upon this information, several drugs including the directly acting antivirals have been proposed to treat people with coronavirus disease 2019 (COVID-19). This rapid review aims to describe the directly acting antivirals that have been examined for use in the management of COVID-19. Searches were conducted in three electronic databases, supplemented with a search on Arxiv, bioRxiv, medRxiv, ChinaXiv, Clinicaltrials.gov and Chinese Clinical Trial Registry for studies examining the use of antivirals in COVID-19 to identify for case reports, case series, observational studies and randomised controlled studies describing the use of antivirals in COVID-19. Data were extracted independently and presented narratively. A total of 98 studies were included, comprising of 38 published studies and 60 registered clinical trials. These drugs include the broad spectrum antivirals such as umifenovir, protease inhibitors such as lopinovir/ritonavir as well as the RNA-dependent RNA polymerase inhibitors, remdesivir and favipiravir. Other drugs that have been used include the nucleosidase inhibitors and polymerase acidic endonuclease inhibitors which are currently approved for prevention of influenza infections. While some of the drugs appear promising in small case series and reports, more clinical trials currently in progress are required to provide higher quality evidence.